Efficacy and safety of voclosporin versus placebo for lupus nephritis (AURORA 1): a double-blind, randomised, multicentre, placebo-controlled, phase 3 trial. Issue 10289 (29th May 2021) - Rovin, Brad H; Teng, Y K Onno; Ginzler, Ellen M; Arriens, Cristina; Caster, Dawn J; Romero-Diaz, Juanita; Gibson, Keisha; Kaplan, Joshua; Lisk, Laura; Navarra, Sandra; Parikh, Samir V; Randhawa, Simrat; et al.
Summary: Background: Voclosporin, a novel calcineurin inhibitor approved for the treatment of adults with lupus nephritis, improved complete renal response rates in patients with lupus nephritis in a phase 2 trial. This study aimed to evaluate the efficacy and safety of voclosporin for the treatment of lupus nephritis. Methods: This multicentre, double-blind, randomised phase 3 trial was done in 142 hospitals and clinics across 27 countries. Patients with a diagnosis of systemic lupus erythematosus with lupus nephritis according to the American College of Rheumatology criteria, and a kidney biopsy within 2 years that showed class III, IV, or V (alone or in combination with class III or IV) were eligible. Patients were randomly assigned (1:1) to oral voclosporin (23·7 mg twice daily) or placebo, on a background of mycophenolate mofetil (1 g twice daily) and rapidly tapered low-dose oral steroids, by use of an interactive web response system. The primary endpoint was complete renal response at 52 weeks defined as a composite of urine protein creatinine ratio of 0·5 mg/mg or less, stable renal function (defined as estimated glomerular filtration rate [eGFR] ≥60 mL/min/1·73 m 2 or no confirmed decrease from baseline in eGFR of >20%), no administration of rescue medication, and no more than 10 mg prednisone equivalent per day for 3 or more consecutive days or for 7 or more days during weeks 44 through 52, just before the primary endpoint assessment. Safety was also assessed. Efficacy analysis was by intention-to-treat and safety analysis by randomised patients receiving at least one dose of study treatment. The trial is registered with ClinicalTrials.gov, NCT03021499 . Findings: Between April 13, 2017, and Oct 10, 2019, 179 patients were assigned to the voclosporin group and 178 to the placebo group. The primary endpoint of complete renal response at week 52 was achieved in significantly more patients in the voclosporin group than in the placebo group (73 [41%] of 179 patients vs 40 [23%] of 178 patients; odds ratio 2·65; 95% CI 1·64–4·27; p<0·0001). The adverse event profile was balanced between the two groups; serious adverse events occurred in 37 (21%) of 178 in the voclosporin group and 38 (21%) of 178 patients in the placebo group. The most frequent serious adverse event involving infection was pneumonia, occurring in 7 (4%) patients in the voclosporin group and in 8 (4%) patients in the placebo group. A total of six patients died during the study or study follow-up period (one [<1%] patient in the voclosporin group and five [3%] patients in the placebo group). None of the events leading to death were considered by the investigators to be related to the study treatments. Interpretation: Voclosporin in combination with MMF and low-dose steroids led to a clinically and statistically superior complete renal response rate versus MMF and low-dose steroids alone, with a comparable safety profile. This finding is an important advancement in the treatment of patients with active lupus nephritis. Funding: Aurinia Pharmaceuticals.